Nanotechnology and Neuroscience: Nano-Electronic, Photonic and Mechanical Neuronal Interfacing 2014
DOI: 10.1007/978-1-4899-8038-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Coatings for Improved Charge Delivery to Neurons

Abstract: This chapter explores the variability and limitations of traditional stimulation electrodes by first appreciating how electrical potential differences lead to efficacious activation of nearby neurons and examining the basic electrochemical mechanisms of charge transfer at an electrode/electrolyte interface. It then covers the advantages and current challenges of emerging micro-/nanostructured electrode materials for next-generation neural stimulation microelectrodes. Introduction to Electrical Stimulation of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 321 publications
(440 reference statements)
0
54
0
Order By: Relevance
“…The impedance of our soft electrodes was lower than that of iridium metal and iridium oxide electrodes and, more importantly, the values are in the middle-to-lower portion of the acceptable range of impedance values for central nervous system electrodes [79], and in some cases, even lower. This suggests that further reduction of the active area of the soft electrodes is possible even with the expected increase in impedance [34]. In addition, the ability to adjust the formulation filler loading to a higher or lower fill ratio provides a mean to tune the impedance value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance of our soft electrodes was lower than that of iridium metal and iridium oxide electrodes and, more importantly, the values are in the middle-to-lower portion of the acceptable range of impedance values for central nervous system electrodes [79], and in some cases, even lower. This suggests that further reduction of the active area of the soft electrodes is possible even with the expected increase in impedance [34]. In addition, the ability to adjust the formulation filler loading to a higher or lower fill ratio provides a mean to tune the impedance value.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the interaction between neurons and the fluorosilicone surfaces is favorable and sustainable in the presence of micromovement. However, variations in surface roughness (physical texture) rather than simply chemical composition may have an impact as well [34, 80]. Importantly, increases in neuronal attachment and density at the neural electrode-tissue interface could impact long-term functionality resulting in improved chronic recording with FS-coated soft wires compared to stiff wires.…”
Section: Resultsmentioning
confidence: 99%
“…One challenge with electrical stimulation is the tradeoff between safety limits and spatial selectivity of the stimulated neural population 48 . Stimulation electrodes with small surface areas can result in high charge densities that lead to permanent damage of the electrode or permanent damage to the tissue and nearby neurons 8, 48, 49 . Therefore, large stimulation electrodes are frequently used, which leads to a spatially broad orthodromic and antidromic activation of neurons 50, 51 .…”
Section: Applications For Photoelectric and Photothermal Technologymentioning
confidence: 99%
“…This variability and unreliability is understood to be the result of complex multimodal failure mechanisms [9]. These include, but are not limited to: material failure such as corrosion, insulation failure, material degradation, electrical lead breakage, electrode delamination and biological responses including biofouling, neural degeneration, and inflammatory gliosis [10]. The present study is focused on dissecting the molecular pathways behind the biological responses that are related to chronic neural recording performance.…”
Section: Introductionmentioning
confidence: 99%
“…This study also revealed the unpredictability of disrupting or avoiding these large intracortical BBB vessels if only the surface vasculatures are avoided during insertion. More recently, it has been shown that implanting ultrasmall electrodes closer to major penetrating blood vessels leads to increased astrocytic GFAP activity [10, 12]. …”
Section: Introductionmentioning
confidence: 99%